On Political Parties in Contemporary Democracies: From the classic perspective to the current debate - Raniolo, Francesco; Viviani, Lorenzo; Damiani, Marco (PARTECIPAZIONE E CONFLITTO, 2015)
The crisis of political parties in contemporary societies and democracies is composed of differ-ent points of views, that require a joint effort for social and political science to try to understand the changing relationship between citizens and parties. Compared to the political mass models, which are typ-ical of the second half of the twentieth century, parties undergo deep processes of transformation. The beginning of a critical season for the traditional forms of political organization goes back to those years; and this critical season can be configured as ideological, organizational and institutional. Between the twentieth and twenty-first century, the political parties has strengthened the structure of their political organization and the weight of their parliamentary activities within the institutions, becoming more and more «state-centered parties», characterized by the progressive reduction of the forms of territorial set-tlement and the growth of the importance of central organisms and the representatives of the assemblies, especially those elected in national parliaments. This results in significant changes of the organizational model and their political functions. In the face of these changes, will the parties still remain a key player for the functioning of contemporary democracy? We will focus on three fundamental steps: the analysis of the creation process of parties and of their function; the description of the most recent perspectives in political parties; the analysis of the relationship between the personalisation of politics and the passage to leader democracy.